Pharmacogenetics and Pharmacokinetic Topical Levofloxacin on Cataract Surgery - Alazi Alazi (Sriwijaya Journal of Ophthalmology, 2021)
The fluoroquinolones (FQs) have proven to be successful for treating ocular infections because the introduction of ciprofloxacin and ofloxacin; the improvement in ofloxacin to levofloxacin, the active l-isomer of ofloxacin; and the targeting of Gram-positive bacteria by moxifloxacin and gatifloxacin with a dual mechanism of action. The in vitro testing of the FQs has determined that moxifloxacin and gatifloxacin are more potent anti-infectives with lower minimum inhibitory concentrations (MICs) to Gram-positive bacteria than the earlier generations of FQs, but no real advantage for in vitro susceptibility has been noted among the FQs for Gram-negative bacteria. The objective of this review is to outline the pharmacogenetics, pharmacokinetics, and efficacy of levofloxacin along with the impact on patients’ life. Such particular approach, being the foundation of personalized medicine, increases efficacy and safety of timolol while reducing costs by using targeted doses.